Kepemimpinan Dalam Perspektif Al-Qur'an - Dede, MuhammadKhalil; Mahmud, Hamidullah (Program Studi Ilmu Al Quran dan Tafsir Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2023)
This research discusses the basic concepts of leadership in general, spiritual leadership and prophetic leadership, as well as how leadership in the perspective of the Qur'an and its examples. Then the purpose of this study is to find out how the meaning of leadership in the perspective of the Qur'an, because there are several words in the Qur'an that mean leader but have slightly different meanings. This research uses qualitative research methods using the type of library research (Library Resarch) which discusses leadership in the perspective of the Qur'an. Then the results of this study the author found several words of leaders in the Qur'an such as Caliph, Imām, Wali, Ulil Amri, Rã'in, Qawwām, Sultān, Milik, and Za im.